2022
DOI: 10.3390/cancers14143497
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiparametric Magnetic Resonance Imaging with Prostate-Specific Membrane Antigen Positron-Emission Tomography Imaging in Primary Prostate Cancer Diagnosis: A Systematic Review and Meta-Analysis

Abstract: Multiparametric magnetic-resonance imaging (mpMRI) has proven utility in diagnosing primary prostate cancer. However, the diagnostic potential of prostate-specific membrane antigen positron-emission tomography (PSMA PET) has yet to be established. This study aims to systematically review the current literature comparing the diagnostic performance of mpMRI and PSMA PET imaging to diagnose primary prostate cancer. A systematic literature search was performed up to December 2021. Quality analyses were conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Results showed that an RFC model for detecting prostate cancer using combined PET and mpMRI radiomic features performed better than RFC models developed using radiomic features from either modality alone. This was not unexpected, due to the aforementioned complementary nature of the imaging modalities as demonstrated in many non-radiomics studies and clinical trials [ 9 , 33 35 ]. This result was also consistent with studies by Zamboglou et al [ 36 ] and Spohn et al [ 37 ] who did not utilise radiomics, but similarly validated imaging with ground truth pathology data and showed that PSMA PET is a valuable addition alongside mpMRI for defining the gross tumour volumes (GTV) for focal therapy applications, where mpMRI is more likely to underestimate tumour volume than PSMA PET [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 89%
“…Results showed that an RFC model for detecting prostate cancer using combined PET and mpMRI radiomic features performed better than RFC models developed using radiomic features from either modality alone. This was not unexpected, due to the aforementioned complementary nature of the imaging modalities as demonstrated in many non-radiomics studies and clinical trials [ 9 , 33 35 ]. This result was also consistent with studies by Zamboglou et al [ 36 ] and Spohn et al [ 37 ] who did not utilise radiomics, but similarly validated imaging with ground truth pathology data and showed that PSMA PET is a valuable addition alongside mpMRI for defining the gross tumour volumes (GTV) for focal therapy applications, where mpMRI is more likely to underestimate tumour volume than PSMA PET [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the AUC of summed ROC curves was 0.91 (95% CI: 0.88–0.93). In a more recent meta-analysis by Zhao et al [ 49 ], PSMA PET/CT outperformed MRI for detecting primary PCa, with a pooled sensitivity of 0.93 vs. 0.87 ( p < 0.01). On the other hand, both techniques were similar for the localization of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…PSMA PET (MR or CT) is more sensitive and specific for primary tumor detection and lymph node staging (90/84% vs. 66/60% for primary, 91/90% vs. 68/46% for nodes), whereas mpMRI has better accuracy for extracapsular extension (79/76% vs. 59/66%) and seminal vesicle infiltration (93/96% vs. 51/60%) 24 . Further meta-analyses show PET is better than MRI alone, 25 but PET and MRI together are better than PET alone 26 . Overall, then, MRI's superior soft tissue contrast and spatial resolution can help find extracapsular extension and seminal vesicle infiltration, and PET's contrast resolution aids its ability to find small or subtle intraprostatic lesions and nodal metastases, and the modalities are likely best used together.…”
Section: Use In Diagnostic Imagingmentioning
confidence: 99%